2009
DOI: 10.1021/ie9000844
|View full text |Cite
|
Sign up to set email alerts
|

Effect of H2O on the Desulfurization of Simulated Flue Gas by an Ionic Liquid

Abstract: Functionalized ionic liquids (ILs) have been demonstrated to absorb SO2 from mixed gases or simulated flue gases efficiently. However, after absorbing a large amount of SO2, the viscosity of the ILs increases greatly, which might limit their eventual applications in large-scale desulfurization from mixed gases or flue gases. In this work, the effect of the presence of water in a simulated flue gas on the absorption of SO2 by a functionalized ionic liquid, 1,1,3,3-tetramethylguanidinium lactate, has been studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 30 publications
3
59
0
Order By: Relevance
“…So the strong hydrogen bonds must be eliminated in order to reduce the increasing of viscosity of the IL during the absorption of CO 2 (Gutowski and Maginn, 2008) . As reported in the literature (Ventura et al, 2008;Ren et al, 2009), the presence of some organic solvents or water can significantly reduce the viscosity.…”
Section: Proposed Mechanismmentioning
confidence: 66%
“…So the strong hydrogen bonds must be eliminated in order to reduce the increasing of viscosity of the IL during the absorption of CO 2 (Gutowski and Maginn, 2008) . As reported in the literature (Ventura et al, 2008;Ren et al, 2009), the presence of some organic solvents or water can significantly reduce the viscosity.…”
Section: Proposed Mechanismmentioning
confidence: 66%
“…The results showed that the error was in the range of ± 5%. The results show that the characteristic peak around 3151.62cm -1 , 2946.09cm -1 , 1638.53cm -1 , 1575.39cm -1 , 1455.24cm -1 , 1329.11cm -1 , 1194.48cm -1 , and 1110.74cm -1 could be clearly observed, as shown in Figure 1S, which is attributed to the existance of [C 3 CSO 3 ]-SiO 2 give smaller specific surface area (SBET) and total pore volume (V). In addition, their specific surface area and total pore volume decreased with the increase of the immobilized amount of EFIILs.…”
Section: So 2 Adsorption and Desorptionmentioning
confidence: 91%
“…[1,2] ILs exhibit efficient and reversible absorption of SO 2 , and can also reasonably be used as a solvent to scrub SO 2 from flue gases. [3,4,5] For example, Huang et al [6] reported that TMG-based (1,1,3,3-tetramethylguanidine) and BMIM-based (1-butyl-3-methylimidazolium) ionic liquids could absorb SO 2 reversibly. The absorption capacity is up to 1.6 mole SO 2 per mole of IL at 20 and 1 bar.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the presence of water reduces the absolute solubility of CO 2 . Ren et al [25] have studied the effect of water on the absorption of SO 2 from a simulated flue gas and found that the presence of the molecular solvent does not decrease the absorption efficiency and causes the viscosity to decrease greatly.…”
Section: Introductionmentioning
confidence: 99%